Proposal for a New Radiated-Emission Test Method Using a Completely Absorber - Lined Chamber Without Groundplane - Garn, Heinrich F. (9th International Zurich Symposium and Technical Exhibition on Electromagnetic Compatibility, 1991)
Completely absorber-lined chambers can be used for standard radiated-emission tests, if a specific test procedure as outlined in this paper is followed. Field-strengths measured in such a chamber can be corrected to obtain open-site equivalents by applying conversion factors, which are functions of frequency and polarization. Excellent equivalence to a standard test will be achieved for small, e.g. hand-held equipment and for desk-top equipment. For large cabinets there is an unavoidable uncertainty in the conversion of up to ±11 dB.